IMPLEMENTASI PELIMPAHAN SEBAGIAN URUSAN WALIKOTA KEPADA CAMAT DALAM MENUNJANG PELAYANAN PUBLIK DI KANTOR CAMAT SAMBUTAN KOTA SAMARINDA - Siti Hasanah; Djumadi .; Dan Buntu Paranoan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze the implementation of the delegations of Mayor of Samarinda’s authorities to Head of Sambutan District. The results show that the delegations of Mayor of Samarinda’s authorities to Head of Sambutan District governed by Regulation No. 32 of 2011 was implemented, however applicative less effective. It can be known of the six indicators set, including 2 declared effective indicators and 4 indicators expressed quite effective.